2009
DOI: 10.1007/s11666-009-9360-z
|View full text |Cite
|
Sign up to set email alerts
|

Partial Evaporation of Strontium Zirconate During Atmospheric Plasma Spraying

Abstract: Perovskite-type SrZrO 3 has been investigated as a candidate material for thermal barrier coating application. During plasma spraying of SrZrO 3 , SrO volatilized more than ZrO 2 and the coating composition deviates from initial stoichiometry. In this investigation, partial evaporation was investigated by spraying SrZrO 3 powders into water. The influences of spraying current, distance and particle size of the powder on the partial evaporation were also investigated in a quantitative way. With optimized sprayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 20 publications
(5 reference statements)
2
0
0
1
Order By: Relevance
“…As pointed out by Zhang et al, the intensity of Hill’s vortex becomes lower when the size of a molten particle is larger owing to a lower temperature and higher viscosity of larger particles. Such size effect on oxide preferential vaporization loss is consistent with that observed for plasma spraying of multicomponent ceramic particles (Ref 126 - 131 ). Those facts suggest that to maintain continuous in-situ deoxidizing to achieve oxide-free metal droplets it is necessary to use optimized molten spray particles parameters including the use of small sized powder particles if the preferential evaporation induced chemical composition change is acceptable.…”
Section: Strategy For Generation Of Oxide-free Molten Metal Droplets In Open Ambient Atmosphere By In-situ Deoxidizing Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…As pointed out by Zhang et al, the intensity of Hill’s vortex becomes lower when the size of a molten particle is larger owing to a lower temperature and higher viscosity of larger particles. Such size effect on oxide preferential vaporization loss is consistent with that observed for plasma spraying of multicomponent ceramic particles (Ref 126 - 131 ). Those facts suggest that to maintain continuous in-situ deoxidizing to achieve oxide-free metal droplets it is necessary to use optimized molten spray particles parameters including the use of small sized powder particles if the preferential evaporation induced chemical composition change is acceptable.…”
Section: Strategy For Generation Of Oxide-free Molten Metal Droplets In Open Ambient Atmosphere By In-situ Deoxidizing Effectsupporting
confidence: 87%
“…To avoid such case and maintain the continuous deoxidizing throughout in-flight of the molten metal droplet, rapid transfer of the deoxidizer element from the inner of molten droplet toward its surface is necessary. The selective oxidation of deoxidizer elements within spray molten droplets is kinetically similar to preferential element vaporization loss observed for plasma spraying of multiple constituent ceramics (Ref 126 - 130 ). The previous investigations showed that two types of mass transfer mechanisms are involved in the movement of elements within molten spray droplets: diffusion and convection (Ref 128 , 131 ).…”
Section: Strategy For Generation Of Oxide-free Molten Metal Droplets In Open Ambient Atmosphere By In-situ Deoxidizing Effectsupporting
confidence: 56%
“…Outro Nas perovskites complexas apresentadas nesta secção verifi ca-se que ambas possuem Mg na sua constituição, no entanto, é necessário ter em conta que este elemento volatiliza facilmente comparativamente com os outros o que pode levar, durante o processo APS, à deposição de um revestimento sem a estequiometria adequada e consequentemente a uma diminuição das propriedades destes materiais enquanto revestimentos. Estudos recentes têm vindo a procurar minimizar este efeito através da manipulação adequada dos parâmetros do processo APS, como por exemplo, o tempo de permanência das partículas no plasma [23].…”
Section: Formas Complexasunclassified